Association of malnutrition with surgical site infection following spinal surgery: systematic review and meta-analysis. Issue 1 (January 2020) - Tsantes, A.G.; Papadopoulos, D.V.; Lytras, T.; Tsantes, A.E.; Mavrogenis, A.F.; Koulouvaris, P.; Gelalis, I.D.; Ploumis, A.; Korompilias, A.V.; Benzakour, T.; Tsivgoulis, G.; Bonovas, S.
Summary: Background: Surgical site infection (SSI) following spinal surgery is a frequent clinical problem with significant clinical and socio-economic consequences. Malnutrition has been linked with SSI in various other surgical procedures. Aim: To investigate whether malnutrition is a risk factor for SSI following spinal surgery. Methods: Two electronic databases (PUBMED and SCOPUS) and the Cochrane Library were searched systematically from inception to May 2019. Cohort and case–control studies assessing malnutrition as a risk factor for SSI in patients undergoing spinal procedures were considered eligible. Μalnutrition was defined according to laboratory measurements or by relevant International Classification of Diseases-9 codes. SSI was the outcome of interest. Two reviewers independently abstracted study data and assessed the risk of bias for each study. Pooled effect estimates were calculated using random effects models. Findings: In total, 22 studies (20 retrospective cohort and two case–control) with over 175, 000 participants (of whom 2.14% developed postoperative SSI) were analysed. SSIs were more likely to develop in malnourished patients [odds ratio (OR) 2.31, 95% confidence interval (CI) 1.75–3.05]. While pre-operative malnutrition was significantly associated with SSI in patients undergoing thoracolumbar spinal and sacral surgery, no significant difference was seen in patients undergoing cervical spinal surgery. In subgroup analyses, similar results were observed for both hospital-based (OR 3.16, 95% CI 1.84–5.43) and population-based (OR 2.00, 95% CI 1.63–2.46) studies. Conclusions: Malnutrition is associated with increased risk of developing SSI after spinal surgery. Further high-quality research is warranted to investigate whether improvement of pre-operative nutritional status can decrease SSI rates.